2017
DOI: 10.1016/j.ijantimicag.2017.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early versus deferred antiretroviral therapy on estimated glomerular filtration rate in HIV-positive individuals in the START trial

Abstract: Background Both untreated HIV infection and antiretroviral therapy (ART) have been associated with worsening kidney function. The impact of earlier ART initiation on kidney function has not been studied. Methods The START trial was a randomized comparison of immediate versus deferred ART initiation among HIV+ persons with CD4+ counts >500 cells/mm3. Serum creatinine and urine dipstick protein were measured at baseline, months 1, 4, 8, 12, and annually thereafter. We compared the two arms for changes in estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
0
16
1
Order By: Relevance
“…The overall incidence rate of eGFR < 60 mL/min (1.9 cases/100 PY) was lower than that reported in a previous study (5.9 cases/100 PY) with a lower baseline median CD4 count that reported on the same endpoint . Also in contrast to previous studies, this study did not find an association between baseline CD4 count and average eGFR or renal dysfunction after ART initiation after adjustment for key baseline characteristics . Notably, analysis of incident eGFR < 60 mL/min – restricted to individuals with a normal baseline renal function – showed a low incidence rate of eGFR < 60 mL/min of 1.1 cases/100 PY (95% CI 0.6–1.8 cases/100 PY) and no incident cases among individuals with baseline CD4 counts > 500 cells/μL.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The overall incidence rate of eGFR < 60 mL/min (1.9 cases/100 PY) was lower than that reported in a previous study (5.9 cases/100 PY) with a lower baseline median CD4 count that reported on the same endpoint . Also in contrast to previous studies, this study did not find an association between baseline CD4 count and average eGFR or renal dysfunction after ART initiation after adjustment for key baseline characteristics . Notably, analysis of incident eGFR < 60 mL/min – restricted to individuals with a normal baseline renal function – showed a low incidence rate of eGFR < 60 mL/min of 1.1 cases/100 PY (95% CI 0.6–1.8 cases/100 PY) and no incident cases among individuals with baseline CD4 counts > 500 cells/μL.…”
Section: Discussioncontrasting
confidence: 99%
“…These studies reported less renal dysfunction following ART initiation among individuals with baseline CD4 counts > 200 cells/μL compared with lower values . Recently published results from the Strategic timing of antiretroviral treatment (START) trial showed higher mean eGFR after ART initiation among individuals starting ART at baseline CD4 counts > 500 cells/μL compared with those with baseline CD4 counts of 350–500 cells/μL . There are, however, limited data from programmatic studies to confirm these findings.…”
Section: Introductionmentioning
confidence: 98%
“…We excluded several studies as they assessed the effect of ART initiation related to CD4 threshold rather than initiating ART soon after HIV diagnosis (Achhra 2017; Danel 2015; Iwuji 2017; Sabapathy 2017; Larmarange 2016; Plazy 2016; Temprano 2015). We further excluded studies that specifically assessed timing of ART in participants who had oppurtunistic infections such as cryptococcal meningitis or tuberculosis meningitis (Bisson 2013; Blanc 2011; Boulware 2014; Degu 2012; Grant 2010; Havlir 2011; Laurelliard 2013; Makadzange 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Nadir CD4 counts were significantly associated with CKD, suggesting that initiating ART early may help in reducing this risk. For example, early initiation of ART in the Strategic Timing for Antiretroviral Therapy (START) study was associated with a modestly higher eGFR and lower risk of proteinuria . In addition, TDF use may be best avoided among patients with lower baseline eGFR as is recommended by some guidelines …”
Section: Discussionmentioning
confidence: 99%
“…For example, early initiation of ART in the Strategic Timing for Antiretroviral Therapy (START) study was associated with a modestly higher eGFR and lower risk of proteinuria. 22 In addition, TDF use may be best avoided among patients with lower baseline eGFR as is recommended by some guidelines. 23 Estimated GFR can be affected by ethnicity and body composition.…”
Section: Numerous Reports Have Documented Higher Incidence Of Ckd Inmentioning
confidence: 99%